2013
DOI: 10.1902/jop.2012.120445
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25‐Hydroxyvitamin D Concentrations and Periodontal Disease in Postmenopausal Women

Abstract: Background Vitamin D has anti-inflammatory and anti-microbial properties that, together with its influence on bone health, may confer periodontal benefit. Methods We investigated cross-sectional associations (1997–2000) between plasma 25-hydroxyvitamin D concentrations [25(OH)D] and periodontal measure among 920 postmenopausal women. Chronic measures of disease were defined based on: 1) alveolar crestal height (ACH) measures from intraoral radiographs and tooth loss, and the 2) Center for Disease Control and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 45 publications
6
103
2
Order By: Relevance
“…In observations reported by Dietrich et al (2004) and Miley et al (2009) a higher serum vitamin D level in periodontal patients correlated with a less severe loss of the clinical attachment. Millen et al (2013) demonstrated an inverse correlation between the serum vitamin D level and the frequency of gum bleeding and periodontitis in postmenopausal women. However, vitamin D supplementation (400 IU/day for 1 year) did not significantly improve the condition of periodontal tissues during routine periodontal procedures in 23 dental clinic patients (Garcia et al 2011).…”
Section: Periodontitismentioning
confidence: 95%
“…In observations reported by Dietrich et al (2004) and Miley et al (2009) a higher serum vitamin D level in periodontal patients correlated with a less severe loss of the clinical attachment. Millen et al (2013) demonstrated an inverse correlation between the serum vitamin D level and the frequency of gum bleeding and periodontitis in postmenopausal women. However, vitamin D supplementation (400 IU/day for 1 year) did not significantly improve the condition of periodontal tissues during routine periodontal procedures in 23 dental clinic patients (Garcia et al 2011).…”
Section: Periodontitismentioning
confidence: 95%
“…Higher intakes of vitamin C (17)(18)(19)(20)(21)(22) b-carotene (18,20), vitamin E (19,20), fruits and vegetables (20), and omega-3 FAs (23,24) have each been associated with greater periodontal health (reviewed in 25). Some (26)(27)(28) but not all (29) studies have shown that higher serum 25-hydroxyvitamin D [25(OH)D] concentrations are associated with better periodontal health. Studies investigating diet and periodontal healing have since emerged.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Vitamin D receptor is expressed on several human immune cells, decreases the proliferation of the T and B lymphocytes, and inhibits the T-helper (Th1) and Th17 (proinflammatory) cell response, while promoting a Th2 (anti-inflammatory) cell response [23]. Vitamin D may help suppress local inflammation at the site of an oral infection.…”
Section: Discussionmentioning
confidence: 99%